Utilization of Genetic Counseling after Direct‐to‐Consumer Genetic Testing: Findings from the Impact of Personal Genomics (PGen) Study. Issue 6 (16th May 2017) - Koeller, Diane R; Uhlmann, Wendy R; Carere, Deanna Alexis; Green, Robert C; Roberts, J Scott; ,
Abstract: Direct‐to‐consumer personal genomic testing (DTC‐PGT) results lead some individuals to seek genetic counseling (GC), but little is known about these consumers and why they seek GC services. We analyzed survey data pre‐ and post‐PGT from 1026 23andMe and Pathway Genomics customers. Participants were mostly white (91%), female (60%), and of high socioeconomic status (80% college educated, 43% household income of ≥100, 000). After receiving PGT results, 43 participants (4%) made or planned to schedule an appointment with a genetic counselor; 390 (38%) would have used in‐person GC had it been available. Compared to non‐seekers, GC seekers were younger (mean age of 38 vs 46 years), more frequently had children <18 (26% vs 16%), and were more likely to report previous GC (37% vs 7%) and genetic testing (30% vs 15%). In logistic regression analysis, seeking GC was associated with previous GC use (OR = 6.5, CI = 3.1–13.8), feeling motivated to pursue DTC‐PGT for health reasons (OR = 4.3, CI = 1.8–10.1), fair or poor self‐reported health (OR = 3.1, CI = 1.1–8.3), and self‐reported uncertainty about the results (OR = 1.8, CI = 1.1–2.7). These findings can help GC providers anticipate who might seek GC services and plan for clinical discussions of DTC‐PGT results.